Perspectives on adherence to ethics standards and behaviour in software development - Senyeki Milton Marebane; Robert Toyo Hans; Jacqui Coosner (Indonesian Journal of Electrical Engineering and Computer Science, 2022)
Considering the powerful position assumed in creating software that changes human lives and society; it is compelling that in addition to technical standards, ethical standards, especially those captured in codes of ethics and practice be adhered to by software engineers. Despite efforts by professional bodies on ethical standards awareness, it is alleged that software engineers are not able to uphold ethical standards in software development projects. This research study probed lecturers concerned with the teaching of software development courses to determine their perceived levels of ethical standards and behavior. The findings show that the importance of ethical standards is recognized. The respondents reported high levels of ethical standards of their own work, colleagues’ work and their students’ work. Although in general the respondents reported high ethical standards, elements of lesser perceived ethical standards on students indicate the need for improvements. The findings of the study are important to educators and industry to recognize the significance of levels of ethics standards and the role educators have in terms of inculcating such ethical standards early in the making of future software engineers.